Sociodemographic, clinical and treatment profile in geriatrics patients: A retrospective hospital based study in a psychiatric hospital in Nepal (Journal of Psychiatrists' Association of Nepal, 2024)
Background: Psychiatric illness and related morbidity is high among the elderly population. Despite this, literature regarding inpatient study in elderly is lacking especially in context to Nepal. This study aimed to study the sociodemographic, clinical and treatment profile in geriatrics patients admitted in a psychiatry hospital.Methods: This was a retrospective study of 140 patients aged 60 years and above admitted in hospital over 2072 to 2080 BS (2015 to 2023 AD). Data were collected by reviewing in-patient files from medical records. Descriptive analysis was done by using SPSS version 25; and results were expressed as means and percentages. Ethical clearance was taken from Nepal Health Research Council.Results: Out of 140 patients, 56.4 % were male and 70.7 % were married. Mean age of the participants was 67.75 years (standard deviation= 7.58). 73.6% of the participants belonged to age group 60 – 70 years. They had more affective disorders (32.9%) followed by psychotic disorders (29.3%). Among affective disorders, depressive disorder was seen in 19.3% patients. Mean age of onset of psychiatric illness was 51.14 years (standard deviation= 17.09) 36.2% had dual diagnosis and 67.9% patients had medical co-comorbidity. To manage acute agitation, 20.7% of patients required use of restraints. Polypharmacy was common, with almost all (95.6%) patients receiving multiple medications.Conclusion: Through this study, we are able to present the socio-demographic, clinical and treatment profile of elderly patients admitted in a hospital. It also emphasizes that psychiatric illness is common in the geriatric population and highlights other issues like suicidal behaviour, restraint use for acute management, issues of polypharmacy and non adherence in this age group.